The Best Nurse Selection Decision Support System At Dr. Hospital. Hadrianus Sinaga Using the Analytical Hierarchy Process (AHP) Method - Lamtiar Purba; Agustina Simangunsong (Putaka Timur Publisher, 2021)
In this study, the authors conducted a study to apply the Analytic Hierarchy Process (AHP) method in the Selection of the Best Nurses and build applications in the application of the method. A nurse is a person who cares for and cares for other people who have health problems. But in its development, the understanding of nurses is getting wider. At this time, the notion of nurses refers to their position as part of health workers who provide services to the community in a professional manner. Decision Support System (DSS) is part of an interactive computer-based information system that is useful for supporting decision-making. The results of this study are the results of the final calculation or ranking, the best nurse chosen is A01 - Lenny M. Simbolon with a value of 0.342. so that the researcher concludes to apply the analytic hierarchy process (AHP) method in the decision support system for selecting the best nurse at RSUD Dr. Hadrianus Sinaga must follow the AHP work steps by comparing the values of each criterion to produce a criteria comparison matrix, Criteria Priority Weight Matrix, Criteria Consistency Matrix and then determine the location comparison scale value based on each criterion. After finding the weight of each criterion against the predetermined alternative, the next step is to multiply the weight of each criterion by the weight of each alternative, then the results of the multiplication are added up by the line. So that the total global priority is obtained. To build a decision support system for selecting the best nurse using the Analytical Hierarchy Process (AHP) method, the authors first analyze system requirements, perform calculations using the AHP method, design systems with UML.